The quantum leader : a revolution in business thinking and practice - Zohar, Danah, 1945- (Prometheus Books, 2016)
Drawing inspiration from quantum physics, innovative management thinker Danah Zohar offers a powerful new model for business thinking and practice. "Quantum leaders," she says, like the systems they have to manage, are poised at "the edge of chaos." They thrive on the potential latent in uncertainty and are adept at unleashing the creativity of self-organization. More important, they are vision- and value-led; they adapt quickly, are unafraid to play with the boundaries and reinvent the rules, and celebrate diversity. Zohar points out that the existing, business-as-usual paradigm owes a great deal to the outdated thinking, assumptions, and values of Newtonian science, which gave rise to the Industrial Revolution. Newtonian thinking assumes that corporations and markets are like machines--predictable, stable, and controllable; they are best managed in a way that eliminates risk and assures equilibrium. Unfortunately, as the global financial collapse of 2008 demonstrated, this way of thinking is as obsolete as the steam engine. Further developing ideas she introduced in her acclaimed Rewiring the Corporate Brain and Spiritual Capital, Zohar has written an inspirational book that will motivate leaders to tap the full potential of their employees, their businesses, and the customers they serve. From the Hardcover edition